ULTRASONIC CAVITATION EFFECT ON THE FATTY ACID COMPOSITION OF LINSEED OIL-BASED EMULSIONS - Feofilaktova, Olga Vladimirovna; Feigelman , Vladislav Lvovich; Aboushanab, Said Abdellatif Said; Kovaleva, Elena Geranovna (Химия растительного сырья, 2023)
Ultrasonic homogenization is a promising method of emulsion formation. Linseed oil containing polyunsaturated fatty acids in the optimal ratio was used as a control sample and the fat base of the emulsions. The effect of ultrasonic treatment can lead to a change in the percentage of fatty acids due to the acceleration and initiation of several chemical reactions. To assess the feasibility of using ultrasound in food production, the fatty acid composition of natural linseed oil and emulsions obtained from it, treated by ultrasound with different durations were studied. The study monitored the formation of radicals since increasing temperature and pressure during the collapse of cavitation bubbles initiates the formation of free hydrogen H- and hydroxyl OH- radicals within and next to them. These may initiate the oxidation of bioorganic compounds in the food product. The research results show that emulsions exposure to the ultrasound at a frequency of 20 kHz for 10, 20 and 30 minutes are capable to maintain the ratio of fatty acids while obtaining a homogeneous, finely dispersed and stable food emulsion. Deviations in the values characterizing the fatty acids content in the emulsions treated by ultrasound for 10, 20 and 30 minutes as compared with the control sample – linseed oil are insignificant (0.02±0.015% to 0.83±0.015). Using the method of electron paramagnetic resonance, the absence of free radicals was established both in the control sample – flax oil, and in emulsions obtained on its basis, homogenized using ultrasonic exposure.